PELAYANAN KESEHATAN DI RUMAH SAKIT UMUM DAERAH (RSUD) WONOSARI KABUPATEN GUNUNGKIDUL - Zalwi, Zulkifli Bima; Dewi, Utami (Natapraja, 2017)
This research aimed to determine the provision of health services in general hospital region of Wonosari, obstacles encountered in the provision of services and efforts made in overcoming these obstacles. The design of this research was descriptive method with a qualitative approach. The results showed that the provision of health services in general hospital region Wonosari had not fully fulfilled the overall principles of public service according to the decision of MENPAN No 63 of 2003, namely transparency, accountability, conditionality, participation, equal rights and balance rights and obligations. In the fulfillment of the Conditional Principles of RSUD Wonosari faces problem, such as infrastructure facilities in hospitals Wonosari inadequate, in particular intensive care unit . In the other hand,the obstacles of health service in RSUD Wonosari were lack of information on health and lack of capacity in human resources particulary the specialists. However by improving health service through the addition of human resources, RSUD Wonosari earned constructing new facilities to improving service performance. Keywords: Health Service, General Hospital dan Regional <span style="font-size: 12pt; line-height: 115%; font-family: ’Times New Roman’, serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">This research aimed to determine the provision of health services in general hospital region of Wonosari, obstacles encountered in the provision of services and efforts made in overcoming these obstacles. The design of this research was descriptive method with a qualitative approach. The results showed that the provision of health services in general hospital region Wonosari had not fully fulfilled the overall principles of public service according to the decision of MENPAN No 63 of 2003, namely transparency, accountability, conditionality, participation, equal rights and balance rights and obligations. In the fulfillment of the Conditional Principles of RSUD Wonosari faces problem, such as infrastructure facilities in hospitals Wonosari inadequate, in particular intensive care unit . In the other hand,the obstacles of health service in RSUD Wonosari were lack of information on health and lack of capacity in human resources particulary the specialists. However by improving health service through the addition of human resources, RSUD Wonosari earned constructing new facilities to improving service performance. <span style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; color: #212121; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Keywords:<span style="font-size: 11.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; letter-spacing: -.05pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">H<span style="font-size: 11.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">ealthService,GeneralHospital dan Regional